Survival analyses of the ZeOxaNMulti trial: Follow-up randomized, double-blinded, placebo-controlled trial of oral PMA-zeolite to prevent chemotherapy-induced side effects, especially peripheral neuropathy - Vitale, Maria Giuseppa; Crispo, Anna; Arundine, Dario; Ronga, Riccardo; Barbato, Carmela; Luongo, Assunta; Habetswallner, Francesco; De Martino, Bernardo Maria; Maione, Angela; Eisenwagen, Sandra; Vitale, Giovanna; Riccardi, Ferdinando (Frontiers in Pharmacology, 2022)
Following the previously published results of the ZeOxaNMulti trial we evaluated the potential of the tested product PMA-ZEO (Multizeo Med) in the prevention of chemotherapy-induced side effects within a 30-month follow-up analysis. The aim was to determine the disease-free survival (DFS), progression-free survival (PFS) and overall survival (OS) in a study-population suffering from colorectal cancer that was previously enrolled in the ZeOxaNMulti trial. The participants of the study were randomised to receive either PMA-ZEO or placebo while undergoing oxaliplatin-based chemotherapy. A total of 104 patients (pts) (51% of participants randomised to the PMA-ZEO group and 49% to the placebo group), out of a total of 120 pts included in the ZeOxaNMulti trial in 2015 were followed up until March 2021 and were included in the follow-up analysis. The analysis of OS did not show statistically significant differences in the first-line chemotherapy patients randomised to PMA-ZEO than among the placebo group (p=0,1) over the whole period of follow-up (30 months). However, focusing on the PMA-ZEO supplementation time point (7 months), a positive and statistically significant trend (p=0.004) was documented in the OS analysis for the first-line chemotherapy patients with increasing months of PMA-ZEO treatment compared to the placebo group. Furthermore, borderline statistical significance was reached for PFS at the PMA-ZEO supplementation time point (7 months) in first-line chemotherapy patients (p=0,05) for cancer progression events. After stratification of the first-line chemotherapy patients, statistically relevant trends for OS for age, comorbidities and oxaliplatin dosage (cycles) were also determined. The overall results for DFS (adjuvant patients), PFS (first-line chemotherapy patients) and OS (adjuvant and first-line chemotherapy patients) were generally slightly better in the PMA-ZEO group than in the placebo group, even though no statistically significant results were obtained between the groups within the follow-up period until 2021 (30 months). Protective effects of PMA-zeolite supplementation can be deduced. A positive trend and more importantly, significant results in PFS and OS for specific patient groups during and/or after PMA-ZEO treatment was determined, which supports the use of PMA-ZEO as an oncological supportive therapy.